Analysis of Work Posture tn the Car Body Assembly Process Using the Rapid Entire Body Assessment Method - Sujatmiko, Bagus; Akmal Suryadi (Journal La Multiapp, 2024)
CV. Faisyal Putra Mandiri located at Kandangan Rejo Lebar street No.11 Surabaya City, is one of the manufacturing industry companies engaged in car body production. In their work activities there are still workers who do not apply ergonomic work postures while working. Unergonomic work positions can cause some parts of the body to not be in their normal position so that they are very vulnerable to musculoskeletal disorders. To overcome these problems, work posture improvement is carried out. Based on the results of the study, it was found that after simulating the use of tools in the metal cutting process, namely the Hydraulic Scissor Lift Table, it can reduce the risk of worker injury through a final REBA value of 7 with a moderate risk level to a final REBA value of 2 with a low risk level. Then in the welding process can reduce the risk of worker injury through the final REBA value of 9 with a high risk level to the final REBA value of 3 with a low risk level. In addition, it is recommended to use a chair as a tool, which is proven through work simulation to reduce the risk of injury. In metal cutting, the REBA value drops from 7 with a moderate risk level to 3 with a low risk level, and in welding, from 9 with a high risk level to 3 with a low risk level.